New Insights into the Mechanism of Odorant Detection by the Malaria-transmitting Mosquito Anopheles gambiae - Davrazou, Foteini (American Society for Biochemistry and Molecular Biology, 2011)
Anopheles gambiae mosquitoes that transmit Plasmodium falciparum malaria use a series of olfactory cues present in human sweat to locate their hosts for a blood meal. Recognition of these odor cues occurs through the interplay of odorant receptors and odorant-binding proteins (OBPs) that bind to odorant molecules and transport and present them to the receptors. Recent studies have implicated potential heterodimeric interactions between two OBPs, OBP1 and OBP4, as important for perception of indole by the mosquito (Biessmann, H., Andronopoulou, E., Biessmann, M. R., Douris, V., Dimitratos, S. D., Eliopoulos, E., Guerin, P. M., Iatrou, K., Justice, R. W., Kröber, T., Marinotti, O., Tsitoura, P., Woods, D. F., and Walter, M. F. (2010) PLoS ONE 5, e9471; Qiao, H., He, X., Schymura, D., Ban, L., Field, L., Dani, F. R., Michelucci, E., Caputo, B., della Torre, A., Iatrou, K., Zhou, J. J., Krieger, J., and Pelosi, P. (2011) Cell. Mol. Life Sci. 68, 1799–1813). Here we present the 2.0 Å crystal structure of the OBP4-indole complex, which adopts a classical odorant-binding protein fold, with indole bound at one end of a central hydrophobic cavity. Solution-based NMR studies reveal that OBP4 exists in a molten globule state and binding of indole induces a dramatic conformational shift to a well ordered structure, and this leads to the formation of the binding site for OBP1. Analysis of the OBP4-OBP1 interaction reveals a network of contacts between residues in the OBP1 binding site and the core of the protein and suggests how the interaction of the two proteins can alter the binding affinity for ligands. These studies provide evidence that conformational ordering plays a key role in regulating heteromeric interactions between OBPs.